THE FIREHOUSE OF FALSEHOOD OF RATNA SARUMPAET’S HOAX IN MEDIA FRAME - Bellinda Putri Ervitasari; Basuki Agus Suparno (The Indonesian Journal of Communication Studies, 2020)
Hoax often appears with massive political momentum, such as the atmosphere of the Presidential Election campaign. Its appearance is often related to other issues and can lead to confrontations on social media such as hatred, blasphemy, and humiliation. On October 2, 2018, the news of Ratna Sarumpaet being persecuted appeared on the internet. It was linked to imposing another camp after her several political colleagues echoed the report everywhere. It didn't take a long time for the police officer to uncover the truth, which turned out to be a hoax. The formulation of this research problem is how Detik.com's online news portal frames, selects, and highlights the news about hoax cases created by Ratna Sarumpaet. This study aims to determine the 1) syntactic structure of the online news portal Detik.com through the hoax case about Ratna Sarumpaet, 2) to know how journalists tell the facts (scripts) used by Detik.com by referring to their vision and mission in emphasizing hoax about Ratna Sarumpaet, 3) to understand the thematic structure by identifying the involvement of Detik.com media in reporting hoax cases of Ratna Sarumpaet, and 4) to find out the rhetorical structure by emphasizing the fact in the case of Ratna Sarumpaet's hoax. The researcher used a qualitative research method, with data collection techniques through online media data tracking techniques and by reviewing documents and archives. The analysis theory used was the framing analysis by Zhongdang Pan and Gerald M. Kosicki. This research indicates that Detik.com focuses more on high site traffic and a massive amount of visitors or readers. The profit from the income received can maintain good relations between the company and the stakeholders.